2017
DOI: 10.1016/j.tranon.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Proving of a Mathematical Model of Cell Calculation Based on Apparent Diffusion Coefficient

Abstract: OBJECTIVES: Recently, Atuegwu et al. proposed a mathematical model based on ADCmean and ADCmin to calculation of cellularity. Our purpose was to compare the calculated cellularity according to the formula with the estimated cell count by histopathology in different tumors. METHODS: For this study, we re-analyzed our previous data regarding associations between ADC parameters and histopathological findings. Overall, 134 patients with different tumors were acquired for the analysis. For all tumors, the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Typically, malignant tumors have lower values in comparison to benign lesions [ 28 ]. Moreover, it has been shown that ADC correlated inversely with cell density in several malignant and benign diseases, and, therefore, can be used as a surrogate cellularity marker [ 19 , 29 ]. Furthermore, ADC can also reflect proliferation activity of different lesions measured by Ki 67 index [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, malignant tumors have lower values in comparison to benign lesions [ 28 ]. Moreover, it has been shown that ADC correlated inversely with cell density in several malignant and benign diseases, and, therefore, can be used as a surrogate cellularity marker [ 19 , 29 ]. Furthermore, ADC can also reflect proliferation activity of different lesions measured by Ki 67 index [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in gliomas, the correlation coefficient was higher ( r =−0.66), whereas in lymphomas, it was −0.25 [4] . This seems to be related to the fact that ADC values are mainly influenced by cellularity, but also, other cellular structures such as [15] extracellular matrix can also cause diffusion restriction in tissues [6] , [13] , [14] .…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, Atuewegu et al proposed two formulas for cellularity calculation based on ADC values (formula 1) and ADC and V e values (formula 2). Recently, results of cellularity calculation according to formula 1 were compared with histopathological data in different tumors [13] . It could be identified that the formula may be used for prediction of tumor cellularity in cerebral lymphomas and rectal cancer, but not in uterine cervical cancer, meningioma, and thyroid cancer [13] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work is in contrast to one recent study that proposed a CNN-based system using multimodel MRI but does not include ADC maps [ 10 ]. ADC maps can be considered as an indication of cell density in tissues [ 19 ] and therefore can be used to search for cancer biomarkers, which usually involve high rates of cell proliferation. Similar to a recent study [ 20 ] that uses multiparametric MRI radiomics for prediction, we use a CNN-based structure instead of hand-crafted features—namely, we utilize a process of independent convolutions for ADC and DWI before fusing them using the dense fully connected layer.…”
Section: Introductionmentioning
confidence: 99%